2022
DOI: 10.21873/cdp.10109
|View full text |Cite
|
Sign up to set email alerts
|

Dysplastic Crypts in Asymmetric Branching in Ulcerative Colitis: A Preliminary Report

Abstract: Aim: To report the detection of dysplastic crypts in asymmetric branching (DCAB) in biopsies from patients with ulcerative colitis (UC). Patients and Methods: One hundred consecutive endoscopic biopsies from patients with UC undergoing surveillance were reviewed. Results: Three biopsy/cases showed DCAB. The frequency of DCAB varied from two in one case, three in another case, and five in the remaining case. Conclusion: The final outcome of DCAB is to generate two or more dysplastic asymmetric offspring-crypts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Importantly, out of the 237 biopsies showing ≥80% CCC, as many as 71% exhibited 100% CCC in individual biopsies. Similar percentages were found in control biopsies (13). Thus, most of the colon biopsies found in a routine setting often display cross-cut crypts.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Importantly, out of the 237 biopsies showing ≥80% CCC, as many as 71% exhibited 100% CCC in individual biopsies. Similar percentages were found in control biopsies (13). Thus, most of the colon biopsies found in a routine setting often display cross-cut crypts.…”
supporting
confidence: 72%
“…We recently tested our subjective impression that most of the colon biopsies were also being crosscut at the laboratory (13). For that purpose, the percentage of routine biopsies with cross-cut crypts were assessed in 447 colon biopsies (376 with UC and 71 controls with mucosal inflammation: 50 with infectious colitis and 21 with sigmoid diverticulitis) (13). It was found that out of 376 colon biopsies with UC, 73% exhibited ≥60% CCC.…”
mentioning
confidence: 99%
“…Chronic inflammation and protracted disease-duration in LLUC, increase the risk for colorectal dysplasia or carcinoma (22,23). In this context, dysplastic CAB were recently detected in patients with LLUC-associate dysplasia (24).…”
Section: Discussionmentioning
confidence: 99%